Regulation of NK cell development, maturation, and antitumor responses by the nuclear receptor NR2F6 - Johannes Woelk; Florian Hornsteiner; Stephanie Aschauer-Wallner; Patrizia Stoitzner; Gottfried Baier; Natascha Hermann-Kleiter (Cell Death and Disease)
Abstract Natural killer (NK) cell development and functionality rely on precise regulation by specific transcription factors (TFs). Our study demonstrates that the nuclear orphan receptor NR2F6 represses the expression of the activating receptor NKp46, an established key player in NK cell-mediated cytotoxicity during infection and tumor rejection. Despite normal NK cell development in the bone marrow, germline Nr2f6-deficient mice exhibit impaired terminal maturation of NK cells in the periphery. Short-term NK cell responses to lipopolysaccharide (LPS) activation, independent of NKp46, are subsequently reduced in Nr2f6-deficient mice. Conventional type 1 dendritic cells (cDC1) and macrophage populations are decreased in spleens of Nr2f6-deficient mice, subsequently, IL-15-dependent NK cell priming is limited. Administration of exogenous IL-15 in vitro and as IL-15 complex in vivo can compensate for these deficits, promoting terminal maturation of NK cells in Nr2f6-deficient mice. Subsequent transcriptome analysis reveals significant changes in gene expression profiles of NK cells from IL-15 complex treated Nr2f6-deficient mice, with notable alterations in essential NK genes such as Klrg1, Prdm1, Stat5a, Zeb2, and Prf1. Consequently, Nr2f6-deficient IL-15 complex-treated NK cells raise enhanced effector responses of IFNγ, Perforin, and Granzyme B upon ex vivo activation. Of importance, Nr2f6-deficient mice are protected against MHC-I negative B16-F10 melanoma lung metastasis formation, especially with IL-15 complex treatment, indicating the potential of NR2F6 to affect NKp46-dependent NK cell-mediated tumor surveillance. The therapeutic targeting of NR2F6 may be a promising strategy for boosting NKp46-dependent NK-cell-mediated tumor surveillance and metastasis.